Pathogenesis of occult chronic hepatitis B virus infection - de la Fuente, Rocio Aller (Baishideng Publishing Group Co., Limited, 2011)
Occult hepatitis B infection (OBI) is characterized by hepatitis B virus (HBV) DNA in serum in the absence of hepatitis B surface antigen (HBsAg) presenting HBsAg-negative and anti-HBc positive serological patterns. Occult HBV status is associated in some cases with mutant viruses undetectable by HBsAg assays; but more frequently it is due to a strong suppression of viral replication and gene expression. OBI is an entity with world-wide diffusion. The failure to detect HBsAg, despite the persistence of the viral DNA, is due in most cases to the strong suppression of viral replication and gene expression that characterizes this “occult” HBV infection; although the mechanisms responsible for suppression of HBV are not well understood. The majority of OBI cases are secondary to overt HBV infection and represent a residual low viremia level suppressed by a strong immune response together with histological derangements which occurred during acute or chronic HBV infection. Much evidence suggests that it can favour the progression of liver fibrosis and the development of hepatocellular carcinoma.